Calendula officinalis stimulate proliferation of mouse embryonic fibroblasts via expression of growth factors TGFβ1 and bFGF - Maryam Hormozi; Mohammadreza Gholami; Ayda Babaniazi; Anneh Mohammad Gharravi (BMC, 2019)
Abstract Background TGF-β has an important role in the process of wound healing and scar formation. The aim of this study is to determine the effects of ethanolic and methanolic extracts of Calendula officinalis on the expression of TGFβ1 and bFGF in the mouse embryonic fibroblast cells (MEFs). Methods Calendula officinalis extract was purchased and different substances defined with gas chromatography and mass spectrometry. MEFs were prepared and after incubating for 15 min, cell viability analyzed. TGF β 1 and bFGF gene expression was evaluated by real-time PCR. TGFβ1 and bFGF protein expression analyzed by ELISA. The statistical analysis of data was done by using SPSS software. Differences were considered significant at (P < 0.05). Results The results of the MTT test showed that the concentrations of 5 μg/ml and10 μg/ml were more suitable for cell proliferation. There was an increase in TGF β 1 gene expression in the MEFs. Expression of TGF β 1 gene remains the same after 24 h. Gene expression of bFGF showed a similar pattern with TGF β 1 expression for both solvents. Analysis of TGFβ1 protein expression showed an increase in TGFβ1 gene expression in the MEFs. Protein expression of bFGF in the MEFs increased at different concentrations at 12 and 24 h after treatment (P < 0.05 and P < 0.01 respectively). Conclusion Calendula officinalis stimulates proliferation of MEFs. Calendula via increased expression of growth factors (TGFβ1 and bFGF) at the first 12 h and a decrease of these factors at 24 h after treatment may ameliorate function of the MEFs in the during wound healing.